(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study aimed to assess the physical and chemical condition of drinking water in El-fashir city, Sudan. The parameters studied are; Electrical conductivity (EC), nitrates, pH, Total Dissolved Solid (TDS) and fluorine were analyzed at water points and in the laboratory. Results were processed on SPSS software. The study revealed the pH results, which were distributed between 6.8 to 8 for samples from hand pumps 1 and 2 and tank water, respectively. The residual chlorine concentration (RC) in the water supply system of the selected stations ranged between 0.2 to 0.6 mg /L. The concentration of nitrate level ranged from 3. 4.5 mg/L, which is within the acceptable range of the standards for WHO and SSMO standards. The study also determined the level of fluorine, which ranged between 0.17 - 0.41 mg/L, which is within the acceptable range of the standards for WHO and SSMO standards. This study found that all results fall within the permissible limits of the standards of WHO and SSMO standards except the hand pumps.